Nanomaterials-driven in situ vaccination: a novel frontier in tumor immunotherapy - Naimeng Liu; Xiangyu Wang; Zhongzhao Wang; Yonemori Kan; Yi Fang; Jidong Gao; Xiangyi Kong; Jing Wang (Journal of Hematology & Oncology)
Abstract In situ vaccination (ISV) has emerged as a promising strategy in cancer immunotherapy, offering a targeted approach that uses the tumor microenvironment (TME) to stimulate an immune response directly at the tumor site. This method minimizes systemic exposure while maintaining therapeutic efficacy and enhancing safety. Recent advances in nanotechnology have enabled new approaches to ISV by utilizing nanomaterials with unique properties, including enhanced permeability, retention, and controlled drug release. ISV employing nanomaterials can induce immunogenic cell death and reverse the immunosuppressive and hypoxic TME, thereby converting a “cold” tumor into a “hot” tumor and facilitating a more robust immune response. This review examines the mechanisms through which nanomaterials-based ISV enhances anti-tumor immunity, summarizes clinical applications of these strategies, and evaluates its capacity to serve as a neoadjuvant therapy for eliminating micrometastases in early-stage cancer patients. Challenges associated with the clinical translation of nanomaterials-based ISV, including nanomaterial metabolism, optimization of treatment protocols, and integration with other therapies such as radiotherapy, chemotherapy, and photothermal therapy, are also discussed. Advances in nanotechnology and immunotherapy continue to expand the possible applications of ISV, potentially leading to improved outcomes across a broad range of cancer types.